Is there Something as an Ex-Yugoslavian HRM Model? – Sticking to the Socialist Heritage or Converging With Neoliberal Practices - Pološki Vokić Nina; Kohont, Andrej; Slavić, Agneš (Naše gospodarstvo/Our economy, 2017)
The question of this paper is whether there is an ex-Yugoslavia HRM model drawing upon Western imported features fused with ethno open-socialistic and self-management elements? In the empirical part Cranet data for 341 companies from Croatia, Slovenia and Serbia are analysed. Main characteristics of HRM systems in ex-Yugoslavia are: the HRM strategic partner role is still neglected, the mind-set of taking care for everybody is omnipresent, the value of performance management is not fully entrusted, the full-time employment still predominates, and the trade unions retained their barging power. Although 30 indicators revealed specifics of ex-Yugoslavia HRM model, the theorized hybrid HRM system was not disclosed.